Growth of Cryptococcus neoformans in presence of L-dopa decreases its susceptibility to amphotericin B. - Wang, Y (1994)
Cryptococcus neoformans grown with L-dopa was melanized and was less susceptible to amphotericin B. The results suggest that in vivo and in vitro susceptibilities to amphotericin B may differ.